THE EFFECTS OF AI ON CHILDREN’S RIGHTS - Rath-Boșca , Albert-Camil (International Journal of Legal and Social Order, 2025)
In today’s world, AI seems to have invaded the day to day lives of us humans. At such a break-neck pace we must ask ourselves how will this new advancement in human history influence the most sensible of groups, the children. In this article, we will make an effort to understand how AI is molding and infringing on the most basic of rights and what is currently happening in Machine Learning (LM) development.